Agonist-induced dimer dissociation as a macromolecular step in G protein-coupled receptor signaling - Petersen, Julian; Wright, Shane C; Rodríguez, David; Matricon, Pierre; Lahav, Noa; Vromen, Aviv; Friedler, Assaf; Strömqvist, Johan; Wennmalm, Stefan; Carlsson, Jens; Schulte, Gunnar (Nature communications, 2017)
G protein-coupled receptors (GPCRs) constitute the largest family of cell surface receptors. They can exist and act as dimers, but the requirement of dimers for agonist-induced signal initiation and structural dynamics remains largely unknown. Frizzled 6 (FZD6) is a member of Class F GPCRs, which bind WNT proteins to initiate signaling. Here, we show that FZD6 dimerizes and that the dimer interface of FZD6 is formed by the transmembrane α-helices four and five. Most importantly, we present the agonist-induced dissociation/re-association of a GPCR dimer through the use of live cell imaging techniques. Further analysis of a dimerization-impaired FZD6 mutant indicates that dimer dissociation is an integral part of FZD6 signaling to extracellular signal-regulated kinases1/2. The discovery of agonist-dependent dynamics of dimers as an intrinsic process of receptor activation extends our understanding of Class F and other dimerizing GPCRs, offering novel targets for dimer-interfering small molecules.Frizzled 6 (FZD6) is a G protein-coupled receptor (GPCR) involved in several cellular processes. Here, the authors use live cell imaging and spectroscopy to show that FZD6 forms dimers, whose association is regulated by WNT proteins and that dimer dissociation is crucial for FZD6 signaling.
Keywords: dimerizace; Frizzled Receptors; Humans; Dimerization; Wnt-5a Protein; protein Wnt 5a; lidé; frizzled receptory; HEK293 Cells; HEK293 buňky